2007
DOI: 10.1038/sj.bjc.6603586
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 gene amplification and shortened survival in glioblastoma patients

Abstract: Interleukin-6 (IL-6) is known to promote tumour growth and survival. We evaluated IL-6 gene amplification in tumours from 53 glioma patients using fluorescence in situ hybridisation. Amplification events were detected only in glioblastomas (15 out of 36 cases), the most malignant tumours, and were significantly associated with decreased patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 11 publications
3
79
1
1
Order By: Relevance
“…15,65 Glioma IL-6 expression in glioma has been correlated with tumor grade and vascularity. 66,67 In a recent study, IL-6 gene amplification was observed in patients with glioblastoma who had the most malignant tumors, and IL-6 gene amplification was associated with decreased survival. 66 IL-6 also can serve as an autocrine growth factor and seems to be required for glioma and spontaneous astrocytoma development in mouse models.…”
Section: Translational Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,65 Glioma IL-6 expression in glioma has been correlated with tumor grade and vascularity. 66,67 In a recent study, IL-6 gene amplification was observed in patients with glioblastoma who had the most malignant tumors, and IL-6 gene amplification was associated with decreased survival. 66 IL-6 also can serve as an autocrine growth factor and seems to be required for glioma and spontaneous astrocytoma development in mouse models.…”
Section: Translational Correlationsmentioning
confidence: 99%
“…66,67 In a recent study, IL-6 gene amplification was observed in patients with glioblastoma who had the most malignant tumors, and IL-6 gene amplification was associated with decreased survival. 66 IL-6 also can serve as an autocrine growth factor and seems to be required for glioma and spontaneous astrocytoma development in mouse models. 68 Although it remains unknown exactly how IL-6 contributes to the malignant progression of gliomas, IL-6 up-regulates VEGF promoter activity and VEGF protein secretion in glioblastoma cells through activation of STAT3.…”
Section: Translational Correlationsmentioning
confidence: 99%
“…Recently, some studies have shown that IL-6 directly influences the invasiveness of colorectal, head and neck cancers (8,9). In GBM, the autocrine regulation of IL-6 has been recognized since 1990 (10), and its aberrant expression and secretion have been found to be associated with GBM formation (11), angiogenesis, grade (12) and prognosis (13,14). However, the role of IL-6 in the malignant progression of GBM remains unclear (7).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Janus kinase (JAK) and the signal transducers and activators of transcription (STAT) are phosphorylated, which activate target genes that mediate cell growth and survival, differentiation, cell mobility and angiogenesis (19,20). The aberrant production and increased secretion of IL-6 in cancer patients is profoundly linked to tumor progression and poor prognosis in many cancer types, including lung cancer (21)(22)(23). IL-6R has been targeted for cancer treatments, resulting in cell growth inhibition or reduced angiogenesis (24,25).…”
Section: Introductionmentioning
confidence: 99%